A review of thermal treatment for bamboo and its composites - Liang Zilu; Jiang Haiyun; Tan Yimin (Green Processing and Synthesis, 2024)
Bamboo, one of the richest non-timber resources, thrives in vast tropical and subtropical regions around the world. The surge of interest in bamboo materials stems from their profound contributions to polymer matrix composites, lauded for their environmental sustainability, mechanical properties, and recyclability. However, the inherent hydrophilicity of bamboo poses a challenge to achieve optimal compatibility with hydrophobic polymer matrices, impede interfacial bonding, and reduce the effectiveness of fiber-reinforced composites. To address these hurdles, economical and environmentally sustainable heat treatment methods have emerged as pivotal tools for enhancing the surface properties of bamboo. Delving into the depths of thermal treatment research, this article meticulously summarizes the influences of varying temperatures, time, and medium on the structure of bamboo. Moreover, it reviews the mechanical properties and surface moisture content of bamboo after heat treatment, providing insights crucial for advancing the frontier of bamboo-based materials.